A randomised‐controlled, prospective study on the effect of dorsal penile nerve block after TURP on catheter‐related bladder discomfort and pain. Issue 5 (11th January 2021) - Göger, Yunus Emre; Özkent, Mehmet Serkan; Göger, Esra; Kılınç, Muzaffer Tansel; Ecer, Gökhan; Pişkin, Mehmet Mesut; Erol, Atilla
Abstract: Purpose: In the present study, the impact of penile nerve block (PNB) on postoperative pain and Catheter‐Related Bladder Discomfort (CRBD) in the transurethral resection of prostate(TURP) patients were evaluated. Methods: Participants of the present study were selected from patients who performed TURP under spinal anaesthesia for benign prostatic hyperplasia (BPH) between January 2018 and July 2020. The present study was planned as a single‐centre, randomised‐controlled prospective study in which the patients were divided into two groups. Group 1 was administered Control (n:40), and Group 2 ultrasonography(USG) guided PNB (n:40). The patients were included in the Groups, respectively. Visual analogue scale (VAS) scores were questioned and recorded in order to evaluate the postoperative pain complaints of the patients after the operation. In addition, in order to evaluate the CRBD, VAS scores were questioned and recorded as 0th, 0‐1th hour, 1st‐2nd hour, 2nd‐4th hour, 4th‐8th hour, 8th‐12th hour, and 12th‐24th hour. In addition, postoperative pain and need for analgesic drug were recorded. Tramadol was given to patients with moderate to severe CRBD. The findings were compared between the Groups. Results: There was no statistical difference demographic and per‐operative data between Group 1 and Group 2. The CRBD and pain‐related VAS scores were significantly higher in Group 1 between the 0 and 8th hours. There was no difference between VAS scores in the postoperative 8‐24th hours. In total 24 hours, Group 2's need for tramadol was significantly less than Group 1. On examining the factors affecting CRBD in the multivariate analysis, age, body mass index(BMI), prostate volume, operation time do not affect CRBD statistically, and only PNB reduces CRBD ( P : .029). While less drug‐related complications were observed in Group 2, no serious complications related to PNB were observed. Conclusion: Penile nerve block is an effective method for the decrease pain and CRBD after urological surgery. It will also reduce the need for analgesics, and provide painless patients in the postoperative period.